Functional trophic composition of the ichthyofauna of forest streams in eastern Brazilian Amazon - Brejão,Gabriel Lourenço (2013)
This study aimed to describe the functional organization of the ichthyofauna of forest streams from northeastern Pará State, Brazil, based on behavioral observation of species' feeding tactics. Seven streams were sampled between June and November, 2010, during snorkeling sessions, totaling 91h 51min of visual censuses at day, dusk, and night periods. Seventy three species distributed in six orders, 26 families and 63 genera were observed, with dominance of Characiformes, followed by Siluriformes. From information gathered by ad libitum observations, each species was included in one of 18 functional trophic groups (FTGs), according to two main characteristics: (1) its most frequently observed feeding tactic; and (2) its spatial distribution in the stream environment, considering their horizontal (margins or main channel) and vertical (water column) dimensions. The most frequent FTGs observed were Nocturnal invertebrate pickers (9 species), Diurnal channel drift feeders (8 spp.), Diurnal surface pickers (7 spp.), and Ambush and stalking predators (6 spp.). The FTGs herein defined enable a comparative analysis of the structure and composition of ichthyofauna in different basins and environmental conditions, which presents an alternative approach to the use of taxonomic structure in ecological studies. The ichthyofauna classification based in FTGs proposed in this study is compared to three other classifications, proposed by Sazima (1986), Sabino & Zuanon (1998) and Casatti et al. (2001).